Implementation of Asmaul Husana Values ​​Through Habituation and Teacher Exemplary Behavior in Character Formation of Class II Students - Feby Angelina Putri; Ainur Rofiq Sofa (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
Character education is an essential aspect of primary education, particularly for lower-grade students who are in the early stage of developing attitudes and behaviors. From the perspective of Islamic education, the values contained in Asmaul Husna have significant potential as a foundation for shaping students’ religious and social character. The internalization of these values cannot rely solely on theoretical instruction but must be implemented through consistent habituation and teachers’ role modeling. This study aims to describe the implementation of Asmaul Husna values through habituation in shaping the character of second-grade students, analyze the role of teachers’ role modeling in internalizing Asmaul Husna values, and examine the impact of implementing Asmaul Husna values through habituation and role modeling on the character formation of second-grade students at SD Unggulan Cahaya Cendekia Glagah, Pakuniran District. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of the principal, the second-grade teacher, and second-grade students. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation. The results indicate that the implementation of Asmaul Husna values through habituation has been carried out in a planned, systematic, and sustainable manner through routine activities such as reciting Asmaul Husna before lessons and integrating their meanings into learning activities. Teachers’ role modeling plays a crucial role in internalizing Asmaul Husna values through consistent attitudes, speech, and behavior. The implementation of habituation and role modeling has a positive impact on students’ character formation, as reflected in improvements in religious attitudes, social awareness, discipline, honesty, and responsibility among second-grade students.